Application of “The nature of science” box event examples to middle school seventh grade students - Özlem Afacan; Demet Şener Çanlı (Institute of Advanced Engineering and Science, 2019)
Previous study on the nature of science indicated that the use of activities is essential and important in the teaching of the nature of science subjects. The aim of the research is to develop alternative activities for helping students in the seventh grade of middle school develop their views on the nature of science and for better teaching the nature of science. In this study, four different activities suitable for middle school seventh class achievements which are also related to the nature of science were developed and worksheets related to those activities were prepared. The activities and worksheets were examined by two science education experts and necessary arrangements were made in line with their opinions. These events are called;